Longitudinal Macro/Microstructural Alterations of Different Callosal Subsections in Parkinson’s Disease Using Connectivity-Based Parcellation - Wu, Jingjing; Guo, Tao; Zhou, Cheng; Guan, Xiaojun; Gao, Ting; Xuan, Min; Gu, Quanquan; Huang, Peiyu; Song, Zhe; Pu, Jiali; Yan, Yaping; Tian, Jun; et al. (Frontiers in Aging Neuroscience, 2020)
Background Corpus callosum (CC) is an important feature of Parkinson’s disease (PD) not only in motor but also in non-motor functions. However, CC is not a homogeneous component, the damage of specific subsection may contribute to corresponding clinical deficit. Objective To investigate the structural alterations of different callosal subsections cross-sectionally and longitudinally in PD and evaluate their relationships to clinical performance. Methods Thirty-nine PD patients who had been longitudinally reexamined and 82 normal controls (NC) were employed. According to their specific callosal-cortical connectivity, 3D CC was divided into five subsections (including prefrontal, premotor, motor, somatosensory and temporal-parietal-occipital subsection). The fractional anisotropy (FA), mean diffusivity (MD), and volume of whole CC and its subsections were computed and compared between groups. Regression model was constructed to explore the relationships between callosal structure and clinical performance. Results At baseline, PD did not show any significant macro-/micro structural difference compared with NC. During disease course, decreased FA and increased MD of whole CC as well as its subsections (excepting temporal-parietal-occipital subsection), and the volume of motor subsection was decreased. Moreover, FA of temporal-parietal-occipital subsection and volume of motor subsection were correlated with the mood domain at baseline, MD of somatosensory subsection was associated with the motor domain at follow-up. Conclusions The structure of CC and its connectivity-specific subsections remains preserved at relatively early stage in PD and progressively disrupted during disease course. Besides, different callosal subsections possess specific associations with clinical performance in PD.